2021
DOI: 10.1038/s41598-021-86036-1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of the insecticide sulfoxaflor alone and in combination with the fungicide fluxapyroxad in three bee species

Abstract: The sulfoximine insecticide sulfoxaflor is regarded as a potential substitute for neonicotinoids that were recently banned in the EU due to their side effects on bees. Like neonicotinoids, sulfoxaflor acts as a competitive modulator of nicotinic acetylcholine receptors. In agricultural environments, bees are commonly exposed to combinations of pesticides, and neonicotinoids are known to interact synergistically with fungicides. The objective of our study is to assess the acute oral toxicity of sulfoxaflor alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 68 publications
5
26
4
Order By: Relevance
“…Recently, a lower LD50 has been reported for forager bees (55 ng/bee) (Azpiazu et al 2021). The lack of toxicity of a similar dose in our experiment seems to confirm that in-hive bees are less sensitive to insecticides than forager bees (Tosi and Nieh 2019), although this might not be a general rule as it could depend on the pesticide type (Rinkevich et al 2015).…”
Section: Discussionsupporting
confidence: 73%
“…Recently, a lower LD50 has been reported for forager bees (55 ng/bee) (Azpiazu et al 2021). The lack of toxicity of a similar dose in our experiment seems to confirm that in-hive bees are less sensitive to insecticides than forager bees (Tosi and Nieh 2019), although this might not be a general rule as it could depend on the pesticide type (Rinkevich et al 2015).…”
Section: Discussionsupporting
confidence: 73%
“…The data available so far on its effects on B. terrestris seem to indicate that chronic exposure of colonies to sulfoxaflor may have important sublethal effects, such as reduction in egg laying and larval and worker production, leading to fewer reproductive offspring [51,81], which may also be aggravated by different stressors [82]. A recent study found sulfoxaflor to be about ten times more toxic after 48 h treatment than we observed [83]. However, our results are consistent with those of this study, which suggests that sulfoxaflor was less toxic than imidacloprid for B. terrestris but more toxic than the recently banned thiacloprid.…”
Section: Discussioncontrasting
confidence: 46%
“…Additionally, as shown in the ECD we demonstrated that exposure levels in the field may exceed those tested in our experiment, if farmers do not implement in-bloom mitigation measures while spraying sulfoxaflor. While in Europe, for instance, it is recommended that sulfoxaflor-based applications are stopped five days before flowering of the crop to reduce exposure peaks, such restrictionswhose effectiveness for non-Apis bees is yet to be demonstrated (Azpiazu et al, 2021;Tamburini et al, 2021) -are often deemed impractical outside the EU, (e.g., for crops with indeterminate bloom, like pumpkin and strawberry in the USA). One of the arguments for the safety of such unrestricted use is the quick degradation of sulfoxaflor in pollen and nectar (EPA, 2019).…”
Section: Discussionmentioning
confidence: 99%